MHD natural convection in an inclined wavy cavity with corner heater filled with a nanofluid - Sheremet, M. A.; Öztop, Hakan Fehmi; Pop, I. (Elsevier, 2016)
A mathematical modelling of MHD free convection in an inclined wavy enclosure filled with a Cu-water nanofluid in the presence of an isothermal corner heater has been carried out. The cavity is heated from the left bottom corner and cooled from the top wavy wall while the rest walls are adiabatic. Uniform magnetic field affects the heat transfer and fluid flow with an inclination angle to the axis (x) over bar. Wavy cavity is inclined to the horizontal direction. Mathematical model formulated using the single-phase nanofluid approach in dimensionless variables stream function, vorticity and temperature has been solved by finite difference method of the second order accuracy in a wide range of governing parameters: Hartmann number (Ha = 0-100), inclination angle of the magnetic field (x = 0 - pi), undulation number (x = 0-4), inclination angle of the cavity (zeta = 0 - pi), solid volume fraction parameter of nanoparticles (phi = 0-0.05), and dimensionless time (tau = 0-0.27). Main efforts have been focused on the effects of these parameters on the fluid flow and heat transfer inside the cavity. Numerical results have been presented in the form of streamlines, isotherms and average Nusselt numbers. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Magnetic field; Natural convection; Nanofluid; Wavy cavity; Inclination; Corner heater